THE IMPACT OF JOB ROTATION ACTIVITIES ON ENHANCING THE GREEN JOB CLIMATE AN ANALYTICAL DESCRIPTIVE STUDY IN THE STATE COMPANY FOR TEXTILE INDUSTRIES/ AD DIWANIYAH TEXTILE FACTORY - Ali A. Sulaiman (Journals Park Publishing, 2022)
Among the most prominent challenges facing the world in our time are the environmental issues represented by climate change, pollution and global warming, which have become a preoccupation for humanity. Since human activities have negative impacts on the environment, all organizations have sought to support pro-environmental behavior in all areas of life on the globe. The purpose of this study is to present a picture about the effect of job rotation activities in achieving the work climate and promoting green environmental behavior among workers in the Diwaniyah textile factory. The research sample was estimated at (40) employees who occupy advanced jobs in the state company for Textile Industries / Ad-Diwaniyah Textile Factory located in Ad-Diwaniyah Governorate. The researcher used the complete statistical package (SPSS) to analyze the data through (arithmetic mean, standard deviation, Spearman-Brown, And the impact test: F), where the conclusion was that (the activities of job rotation in the company enhanced the transformation of the traditional job environment into a green job environment), while the most prominent recommendation was (preparing training programs for all organizational levels to enable them to develop traditional work behaviors into green behaviors).